Estimating Poverty among Refugee Populations: A Cross-Survey Imputation Exercise for Chad - Theresa Beltramo; Hai-Anh H. Dang; Ibrahima Sarr; Paolo Verme (Global Labor Organization (GLO), 2020)
Household consumption surveys do not typically cover refugee populations, and poverty estimates for refugees are rare. This paper tests the performance of cross-survey imputation methods to estimate poverty for a sample of refugees in Chad, by combining United Nations High Commissioner for Refugees survey and administrative data. The proposed method offers poverty estimates based on administrative data that fall within a 95 percent margin of poverty estimates based on survey consumption data. This result is robust to different poverty lines, sets of regressors, and modeling assumptions of the error term. The method outperforms common targeting methods, such as proxy means tests and the targeting method currently used by humanitarian organizations in Chad.
Keywords: C15; F22; I32; O15; O20; 330; Refugees; Forced displacement; Targeting; Poverty; Chad